Formation of IgE-binding factors by human T-cell hybridomas. - Huff, T F (1984)
Normal human T cells that proliferated in the presence of interleukin 2 (IL-2) formed IgE-binding factors when incubated with human IgE. These cells were then fused with a mutant of the human T-cell line CEM. Incubation of five hybridomas with human IgE or culture of the cells in IgE-coated wells resulted in the formation of IgE-binding factors. One hour of incubation with 10 micrograms of human IgE per ml was sufficient to induce the hybridomas to form IgE-binding factors. Polymerized IgE was much more efficient than monomeric IgE for the induction of the factor formation. As little as 10 ng of IgE dimer per ml was sufficient to induce factor formation. The IgE-binding factors produced by the hybridomas bound to human IgE-coated Sepharose and were recovered from the beads by elution at acid pH. The factors had low affinity for rat IgE but failed to bind to human IgG. The IgE-binding factors formed by four hybridomas had a Mr between 25,000 and 30,000, whereas one hybridoma formed IgE-binding factors of Mr 30,000 and Mr 15,000. The IgE-binding formed by all of the hybridomas had affinity for concanavalin A, indicating that the factors are glycoproteins.